Family in search of a treatment Example of Families facing infertility in the city of Tetouan, northern Morocco (2023–2024) - NFIFAKH, Mohamed Ahmed (Journal of Humanities & Social Sciences, 2025)
This research aims to explore experiences concerning the treatment-seeking journeys of families undergoing primary infertility in Tetouan, northern Morocco. It intends to identify the pursued or anticipated medical treatment pathways, along with the factors influencing these decisions. This research was conducted with a group of participants consisting of thirty couples (sixty individuals) experiencing infertility in northern Morocco. It included couples of various ages—some are still on the journey to have a child, while others had already ended that journey without having children. Both spouses were considered together as a single unit of analysis. As for the data collection methodology, the research relied on open-ended interviews with both spouses together; however, individual interviews were also conducted with each of them separately. The research concluded that the experience of medical treatment for infertile families varies according to the period of marriage and the educational level of both spouses. The new families with higher or intermediate education levels are the most likely to seek medical treatment and internalize medical values in the field of infertility, as they follow the medical path without any deviation. This research also realizes that the female body is the most medically treated in this field, despite the fact that men are medically more responsible for family infertility. This prioritization of the female body is not only imposed by social representation of fertility, but by medical practices as well. The female body is regarded as the primary agent of fertility, even when it is not medically responsible for infertility.
Keywords: Infertility; medical treatment; treatment experience; infertile family